Bioremediation. An overview - Shinde, Shekhar (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">A brief outline of the development of bioremediation technologies is presented. The major features and limitations are discussed, and an overview of the current state of the art in field applications is sketched.